Promoter Specific Methylation of SSTR4 is Associated With Alcohol Dependence in Han Chinese Males - Zhao, Rongrong; Shi, Huihui; Yin, Jiajun; Sun, Zhen; Xu, Yahui (Frontiers in Genetics, 2022)
Alcohol dependence (AD) is one of the most serious and complex public health problems in China and worldwide, in which environmental and genetic factors play an important role. Previous findings from our laboratory using the Illumina Infinium Human Methylation450 BeadChip suggested that methylation at the promoter of SSTR4 was one of the major form of DNA modification in alcohol-dependent populations. To investigate whether DNA methylation levels of the SSTR4 promoter influence alcohol-dependent behaviors, genomic DNA was extracted from the peripheral blood sample of 63 subjects with AD and 65 healthy controls, and pyrosequencing was used to verify the results of BeadChip array. Linear regression was used to analyze the correlation between the methylation levels of SSTR4 promoter and the scores of alcohol dependence scales. Gene expression of SSTR4 in brain tissue was obtained from the Genotype-Tissue Expression (GTEx) project and Human Brain Transcriptome database (HBT). We found the methylation levels of SSTR4 in AD group were significantly lower than healthy controls (two-tailed t-test, t = 14.723, P ＜ 0.001). In addition, only weak to moderate correlations between the methylation levels of the SSTR4 promoter region and scale scores of Alcohol Use Disorders Identification Test (AUDIT), Life Events Scale (LES) and Wheatley Stress Profile (WSS) based on linear regression analyses (AUDIT: R2= 0.35, P ＜ 0.001; LES: R2 = 0.27, P ＜ 0.001; WSS: R2 = 0.49, P ＜ 0.001). The hypomethylated status of SSTR4 may involve in the development of AD and increase the risk of AD persistence in Han Chinese males.